Las artes grafo plásticas y su incidencia en el desarrollo de la pre lectura en los niños y niñas de educación inicial de la Escuela Fiscal Juan Manuel Lasso de la provincia de Cotopaxi, cantón Latacunga, parroquia Tanicuchi, sector Lasso en el año lectivo 2014-2015 - Centeno Bernal, Rosa Valeria (2015)
Since ancient times, the Grafo-Plastic Arts has been a fundamental tool in child development. In education, teachers claim that children acquire skills for their education throughout their lives. Students and teachers look for creative and communicative children. The plastic-arts application will develop the pre-reading and it will encourage reading at an early age. In the early child life, he/she is motivated by reading a story or a book. This period is ideal for pre-reading habit. This research was based on different activities with Plastic-Graph application to pre-reading Arts development in Early Childhood Education. The goal was to achieve the reading and imagination pleasure. It provides a good intellectual development and verbal fluency according to age. Also, they will express their ideas, and they will be reflected in each art work. This will be a right communication way where they can interact with others.